2004
DOI: 10.1111/j.1471-4159.2004.02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic serotonin sulfate in opisthobranch mollusks

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) is a ubiquitous modulatory neurotransmitter with roles as a neurohormone and neurotransmitter. However, few studies have been performed characterizing this molecule and its related metabolites in circulating fluids. Here, we demonstrate native 5-HT sulfate, but much lower levels of 5-HT, in hemolymph of the marine mollusk Pleurobranchaea californica. The metabolite 5-HT sulfate forms from 5-HT uptake and metabolism in central ganglia of Aplysia californica and in the visce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…Also, indings in sea molluscs indicate that metabolism of serotonin with further formation of 5-HT-SO 4 depends upon the location of release. Thus, haemolymph 5-HT-SO 4 most probably originates from the nervous system [7,8]. There is also no doubt about the entrance of ingested 5-HTP into CNS [21].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, indings in sea molluscs indicate that metabolism of serotonin with further formation of 5-HT-SO 4 depends upon the location of release. Thus, haemolymph 5-HT-SO 4 most probably originates from the nervous system [7,8]. There is also no doubt about the entrance of ingested 5-HTP into CNS [21].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Later, a similar compound was found in human urine, cerebrospinal liquor and platelets [4][5][6]. During recent years, some research was done with marine molluscs determining 5-HT-SO 4 in their nervous system [7,8]. Findings showed that the serotonin metabolite 5-HT-SO 4 forms from 5-HT uptake and metabolism in central ganglia and other structures of nervous system but not in haemolymph itself.…”
Section: Literature Evidence Related To 5-ht-so 4 Appearance In Animamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it was concluded that 5-HT-SO4 detected in hemolymph is most probably originating from the nervous system [17,18] . This suggests us that given compound could emphasizes intensity of serotonin metabolism in the nervous system.…”
Section: Literature Evidence Of Detection Of 5-ht-so4 In Animals and mentioning
confidence: 99%
“…Findings showed that the 5-HT-SO4 forms from 5-HT uptake and metabolism in central ganglia and other structures of nervous system, but not in hemolymph per se. The scheme of metabolism according to the Stuart et al is showed below [17,18] . Serotonin can also be glucuronidated by action of the enzyme uridine diphosphate glucuronyltrans-ferase.…”
Section: Formation Of Serotonin-o-sulfatementioning
confidence: 99%